2022
DOI: 10.1021/acsomega.2c03117
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Quantification, FT-IR Analysis, and In Silico Characterization of Potential Bio-active Compounds Identified in HR-LC/MS Analysis of the Polyherbal Formulation from Northeast India

Abstract: Diabetes is a group of metabolic disorders characterized by elevated blood sugar levels, leading to many undesirable health consequences. There are many herbal formulations, traditionally used by the Northeast Indian population for disease management. These formulations require scientific validations to optimize their efficacy and increase their popularity. In this study, we attempt to scientifically validate a polyherbal formulation traditionally used for the management of diabetes through preliminary phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…In a similar study, FTIR analysis showed different characteristic band values with functional groups in the PHF such as amines, alcohol, phenols, alkanes and alkenes having bioactive phytochemicals with therapeutic values [32]. In another study, a polyherbal formulation was developed and evaluated for its antidiabetic effect [33].…”
Section: Figure 3 Ftir Spectra Showing Different Peaks Of Polyherbal ...mentioning
confidence: 92%
“…In a similar study, FTIR analysis showed different characteristic band values with functional groups in the PHF such as amines, alcohol, phenols, alkanes and alkenes having bioactive phytochemicals with therapeutic values [32]. In another study, a polyherbal formulation was developed and evaluated for its antidiabetic effect [33].…”
Section: Figure 3 Ftir Spectra Showing Different Peaks Of Polyherbal ...mentioning
confidence: 92%
“…Using a PerkinElmer Spectrum-100 FTIR spectrometer, FTIR analysis was performed on the purified PehR protein, ATP, and their mixtures. The spectrum was recorded in the frequency range between 4000 and 400 cm –1 . In a nutshell, FTIR measurements were carried out at pH 7.4 in 137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 , 8 mM MgAc 2, and 1.8 mM KH 2 PO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The hydroethanolic extract of E. ganitrus leaves was used for LC-MS analysis (Singh et al ., 2022) . The LC/MS instrument is equipped with an Electron Spray Ionization (ESI) ion source operating in a positive and negative ion mode.…”
Section: Methodsmentioning
confidence: 99%